Indústria fonográfica brasileira: novos movimentos no mercado musical no início do século XXI - Sá, Claudio Alessandro Diniz de (2009)
This thesis presents the relevant points concerning the consolidation of the Brazilian music industry and its effect on the music scene between 1998 and 2008 caused by the introduction of new digital technology, music piracy and illegal Internet downloading. This thesis also analyzes the position of music producers towards new digital media in relation to production, distribution, marketing and consumption